Genetically encoded fragment-based discovery. (June 2019) - Derda, Ratmir; Ng, Simon
Abstract : This opinion describes recent advances of molecular discovery technology dubbed Genetically Encoded Fragment-Based Discovery (GE-FBD). GE-FBD starts from a known ligand or 'fragment' that binds to a desired target weakly and often with low specificity. Covalent incorporation of fragment into a diverse, genetically encoded library of peptides yields a library of peptide–fragment combinations. Selection from such a library has a high likelihood to identify ligands, in which the peptides bind to distinct adjacent pockets of the target in synergy with the fragment and exhibits enhanced affinity and specificity when compared to the fragment itself. GE-FBD could employ fragments that bind non-covalently as well as reversible covalent warheads. The key advances in GE-FBD include (i) synthetic chemistry that enables incorporation of diverse fragments into both linear and cyclic peptide libraries; (ii) quantification of multi-step modifications in million-to-billion library members, (iii) and chemical transformations that permit incorporation of fragments with concurrent topological change from linear to macrocyclic topologies.